Characteristics of Taman Sari Village, Licin District, Banyuwangi Based on Village Build Index (IDM) - Rossyda Priyadarshini; Maroeto; Wahyu Santoso (Nusantara Science and Technology Proceedings)
Taman Sari Village, Licin District is a developing village with an IDM value of 0.695. This means that efforts are needed to improve the level of the village economy as well as community welfare so that it becomes a developed and independent village. The determination of the IDM Value is determined using indicators and scoring. Viewed from the aspect of social security (IKS) there are still some weaknesses both in terms of health dimensions, human resources in the health sector; and from the educational dimension, namely the unavailability of advanced education, and in terms of variable access to knowledge. From the social aspect there are no obstacles, so too from the aspect of religion, and tolerance, and public space. But from the environmental aspect, especially the optimization of agricultural land is very limited so it still needs to be improved.